Studi literatur: Pendekatan induktif untuk meningkatkan kemampuan generalisasi dan self confident siswa SMK - Aisyah, Ani (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2016)
The generalizing skill of vocational students was still quite low of a grade. These results were demonstrated by several studies that have been done before. Many students felt difficult in finding patterns or relationships of mathematical situations, especially in its analysis to make generalizations. According to the goals of the vocational curriculum of mathematics teaching, generalization was one of the capabilities that must be developed. Therefore, self-confident as affective aspects becomes the main factor which supports the development of generalization ability. This article focused on the reviewing an approach in mathematics learning process that can be used as an alternative to improve the ability of generalization and self-confident of vocational students.